[Killer Whale Performance at Seven Seas Marine Life Park, 4] (1965)
Photograph of a killer whale performance at the Killer Whale Stadium, Seven Seas Marine Life Park in Arlington, Texas. Newtka, the killer whale, can be seen laying on the platform within the stadium and interacting with one of the trainers. Another trainer is standing on a platform nearby Orchin, the Seven Seas mascot. A castle-themed backdrop is present behind the platform.